Voluntary counselling and testing for young adults in Limpopo Province - Counsellors' perceptions - Patrone R. Risenga; Mashudu Davhana-Maselesele; Chikwelu L. Obi (AOSIS, 2013)
Counselling and testing services for HIV have long been a component of HIV prevention and care programmes in developed countries and have proved to be a cost-effective way of reducing risky behaviours. It is, therefore, important to document the perceptions of voluntary counselling and testing counsellors towards the use of counselling and testing amongst young adults. The purpose of the study was to describe the perceptions of these counsellors dealing with young adults in Vhembe District, Limpopo Province, where the study was conducted. Two themes emerged from the findings of the voluntary counselling and testing counsellors, namely that they feel that the programmes are inaccessible to young adults and that there are difficulties which might impact on the programmes' efficacy. The findings of this study should contribute to the reduction of HIV by promoting voluntary counselling and testing uptake by young adults. Berading- en toestingsdienste vir HIV is lankal reeds 'n geintegreerde deel van die voorkoming en versorgingsprogramme van HIV in ontwikkelde lande en dit is bewys dat dit 'n koste-effektieve manier is om gevaarlike gedrag te verminder. Dit is dus belangrik om die persepsies van vrywillige berading en toesting deur beraders ten opsigte van die gebruik van beraders onder jong volwassenes, te staaf. Die doel van hierdie studie was om die persepsies van hierdie beraders wat met jong volwassenes in die Vhembe distrik, Limpopo provinsie, werk, te beskryf. Twee temas het uit die bevindinge te voorskyn gekom, naamlik: dat die programme ontoeganglik vir jong mense is, en dat daar moontlike probleme is wat op die doeltreffenheid van die programme inslaan. Die bevindinge van hiedie studie behoort 'n bydrae te maak tot die vermindering van HIV deur die vrywillige berading en toesting by jong mense aan te beveel.